1998
DOI: 10.1086/301931
|View full text |Cite
|
Sign up to set email alerts
|

The Nova Scotia (Type D) Form of Niemann-Pick Disease Is Caused by a G3097→T Transversion in NPC1

Abstract: Niemann-Pick type D (NPD) disease is a progressive neurodegenerative disorder characterized by the accumulation of tissue cholesterol and sphingomyelin. This disorder is relatively common in southwestern Nova Scotia, because of a founder effect. Our previous studies, using classic linkage analysis of this large extended kindred, defined the critical gene region to a 13-cM chromosome segment between D18S40 and D18S66. A recently isolated gene from this region, NPC1, is mutated in the majority of patients with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 9 publications
4
85
1
Order By: Relevance
“…Our findings confirm previous reports that focused on the differences in esterification and cholesterol homeostasis between cells obtained from patients with the classical NP-C phenotype as compared with cells obtained from the Nova Scotian milder phenotype. 9,10 Indeed, two individuals with "moderate" biochemical phenotype (AM, SG) had the same mutation as that described in the Nova Scotian genetic isolate 17,24 (Table 1).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our findings confirm previous reports that focused on the differences in esterification and cholesterol homeostasis between cells obtained from patients with the classical NP-C phenotype as compared with cells obtained from the Nova Scotian milder phenotype. 9,10 Indeed, two individuals with "moderate" biochemical phenotype (AM, SG) had the same mutation as that described in the Nova Scotian genetic isolate 17,24 (Table 1).…”
Section: Discussionmentioning
confidence: 66%
“…A G992W mutation previously detected in the Nova Scotian genetic isolate 17 was found in two independent Muslim Arab families originating from the northern part of Israel (AM and SG). We examined four affected individuals in these families and found the phenotypic severity to be similar to that previously described in the Nova Scotian patients.…”
Section: Clinical Features Of Np-c Patientsmentioning
confidence: 81%
See 1 more Smart Citation
“…NPC1 accounts for 95% of the clinical cases. In the general population, multiple distinct NPC1 gene mutations are found (23), whereas affected individuals in the French Acadian population of Nova Scotia have a common mutation (24). The second disease locus, NPC2, accounts for approximately 5% of known cases (25,26).…”
Section: Npc Genesmentioning
confidence: 99%
“…Only three relative frequent mutations have been found within distinct patient groups: the p.G992W, almost exclusively seen in Acadian patients from Nova Scotia (Greer et al 1998), the p.P1007A found in about 15% of mutated alleles in different European populations (Ribeiro et al 2001;Fancello et al 2009) and the p.I1061T that accounts for 15-20% of mutated alleles in Western Europe and USA (Millat et al 1999;Sun et al 2001;Park et al 2003;Millat et al 2005). However, a study performed in 44 Italian NPC patients showed that the p.I1061T mutation is much less common in Italy, representing only a 4.7% of the NPC1 alleles (Fancello et al 2009).…”
Section: Introductionmentioning
confidence: 99%